Iron-Catalyzed Stereoselective Nitrogen Atom Transfer for 1,2-cis-Selective Glycosylation - Xu, Hao; Zhang, Dakang; Jiang, Zixiang; Yin, Le; Clark, Spencer I.; Wang, Pinzhi; Lamar, Jordan D.; Cohen, Adam M. (Synlett, 2025)
This account highlights an iron-catalyzed exclusively 1,2-cis-selective glycosylation method for aminoglycoside synthesis. This selective nitrogen atom transfer reaction is effective for a broad range of glycosyl donors and acceptors, and it can be operated in a reiterative fashion and scaled up to the multigram scale. Mechanistic studies revealed a unique yet generally applicable glycosylation mechanism in which the iron catalyst activates a glycosyl acceptor and an oxidant when it facilitates the cooperative atom transfer of both moieties to a glycosyl donor in an exclusively cis-selective manner.
Keywords: Stereoselective glycosylation; Nitrogen atom transfer; Iron catalysis; Aminoglycoside; Complex-carbohydrate synthesis